2005
DOI: 10.1021/jm050184y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Anilide Inhibitors against the Severe Acute Respiratory Syndrome 3CL Protease

Abstract: A diversified library of peptide anilides was prepared, and their inhibition activities against the SARS-CoV 3CL protease were examined by a fluorogenic tetradecapeptide substrate. The most potent inhibitor is an anilide derived from 2-chloro-4-nitroaniline, l-phenylalanine and 4-(dimethylamino)benzoic acid. This anilide is a competitive inhibitor of the SARS-CoV 3CL protease with K(i) = 0.03 muM. The molecular docking experiment indicates that the P1 residue of this anilide inhibitor is distant from the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 22 publications
1
75
0
1
Order By: Relevance
“…Jain and colleagues reported a series of keto-glutamine analogues with a phthalhydraido group at the α-position, whose derivatives are known HAV 3C inhibitors, could act as reversible inhibitors against SARS M pro with IC 50 ranging from 0.6 to 70 µM [80]. Shie and colleagues reported that an anilide derived from 2-chloro-4-nitroaniline, L-phenylalanine and 4-(dimethylamino) benzoic acid can reversibly inhibit SARS-CoV M pro with a K i of 30 nM [87]. Chen and co-workers reported that a series of isatin (2,3-dioxindole) derivatives, which are known covalent inhibitors against rhinovirus 3C protease, could inhibit SARS-CoV M pro activity [98].…”
Section: Ab Initio Inhibitor Designmentioning
confidence: 99%
“…Jain and colleagues reported a series of keto-glutamine analogues with a phthalhydraido group at the α-position, whose derivatives are known HAV 3C inhibitors, could act as reversible inhibitors against SARS M pro with IC 50 ranging from 0.6 to 70 µM [80]. Shie and colleagues reported that an anilide derived from 2-chloro-4-nitroaniline, L-phenylalanine and 4-(dimethylamino) benzoic acid can reversibly inhibit SARS-CoV M pro with a K i of 30 nM [87]. Chen and co-workers reported that a series of isatin (2,3-dioxindole) derivatives, which are known covalent inhibitors against rhinovirus 3C protease, could inhibit SARS-CoV M pro activity [98].…”
Section: Ab Initio Inhibitor Designmentioning
confidence: 99%
“…Although AG7088 has no detectable or very weak inhibitory activity against SARS 3C-like proteinase, some of the derivatives bind to the enzyme with IC 50 of around 11 µM in the in vitro FRET assay using 14mer peptide substrate. Shie et al [58] discovered that anilide compounds act as potent inhibitors in the in vitro FRET assay and the most active compound gives K i of 0.03 µM. Bacha et al [59] designed bifunctional boronic acid compounds to bind with the serine cluster (Ser139, Ser144 and Ser147) near the active site cavity and the compounds inhibited SARS 3C-like proteinase as strong as 40 nM.…”
Section: Active Inhibitors Discoveredmentioning
confidence: 99%
“…They can be categorized as covalent peptidomimetic, non-covalent peptidomimetic, and non-peptidic. [10] Unlike 3CLpro, the development of PLpro inhibitors has been very limited until recently, despite its essential role in SARS viral replication. In addition to our own work, [11] two very different types of PLpro inhibitors have been reported in recent years.…”
Section: Introductionmentioning
confidence: 99%